When the Watchers Become the Watched: A Qualitative Inquiry into Police Officer Perceptions of Body-Worn Cameras - Aksin, Nevena (Université d'Ottawa / University of Ottawa, 2018)
Recently, police legitimacy has come under attack due to ongoing allegations of police use of excessive force. In line with national efforts to modernize police services, body-worn cameras have been positioned as a promising response to reconstructing police legitimacy due to their potential to provide greater transparency and accountability (Brucato, 2015). Despite the rapid and extensive adoption of body-worn cameras by North American police services (Brucato, 2015), there is a great deal of uncertainty regarding effective policy, implementation and expected outcomes. As it stands, the current research that examines the impact of body-worn cameras on citizen complaints and police use of force presents a narrow understanding of their use. Existing research calls for future studies to examine officer perceptions of body-worn cameras in order to gain a more comprehensive understanding of their value and impact (Boyd, Mateescu & Rosenblat, 2015). As such, the primary research objective of this study is to understand how police officers perceive the use of body-worn cameras. Semi-structured interviews were conducted with police officers from the Toronto Police Service. By drawing on Orlikowski and Gash’s (1994) technological frames of reference framework, the study concludes that officers felt that both of the BWC models during the pilot project were inadequate, were skeptical about the potential of BWCs due to the belief that BWCs are a tool primarily used to “keep an eye on the police”, believed that BWCs impact officer and citizen conduct in ways that can potentially harm police-community relationships, and reported using BWCs to gain greater control over police visibility. Recommendations for training and body-worn camera program development are presented at the end of the study, along with directions for future research.
Keywords: Body-worn cameras; Policing; Surveillance; Qualitative